Health impact assessment of decreases in PM10 and ozone concentrations in the Mexico City Metropolitan Area. A basis for a new air quality management program - Horacio Riojas-Rodríguez; Urinda Álamo-Hernández; José Luis Texcalac-Sangrador; Isabelle Romieu (Instituto Nacional de Salud Pública, 2014)
Objective. To conduct a health impact assessment (HIA) to quantify health benefits for several PM and O3 air pollution reduction scenarios in the Mexico City Metropolitan Area (MCMA). Results from this HIA will contribute to the scientific support of the MCMA air quality management plan (PROAIRE) for the period 2011-2020. Materials and methods. The HIA methodology consisted of four steps: 1) selection of the air pollution reduction scenarios, 2) identification of the at-risk population and health outcomes for the 2005 baseline scenario, 3) selection of concentration-response functions and 4) estimation of health impacts. Results. Reductions of PM10 levels to 20 μg/m3 and O3 levels to 0.050ppm (98 µg/m3) would prevent 2300 and 400 annual deaths respectively. The greatest health impact was seen in the over-65 age group and in mortality due to cardiopulmonary and cardiovascular disease. Conclusion. Improved air quality in the MCMA could provide significant health benefits through focusing interventions by exposure zones.